A NEEDS ANALYSIS IN DEVELOPING A WRITING CURRICULUM FOR EFL EDUCATION STUDENTS: A CASE STUDY AT THE DEPARTMENT OF ENGLISH EDUCATION OF SEMARANG STATE UNIVERSITY - Astuti, Puji (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2009)
This study was intended to evaluate an existing writing curriculum in an English education program. The curriculum evaluation was conducted through a needs analysis, focusing on the needs of the students in the program. It is hoped that the result of the study would provide useful information for the program about writing curriculum they are implementing. There were four aspects of the curriculum that this study investigated: (1) the goals/objectives of the writing courses, (2) the approaches/methodology, (3) the classroom management, and (4) the class/program resources. More specifically, this study intended to know whether the course objectives/goals were appropriate with the needs of the students, whether the approaches/methodology were contextual and met the needs of the students, whether the classroom management was effective, and whether the class/program resources adequate to implement the goals/objectives. The study was categorized as a case study since it was a certain case happened in a certain context. The same case may not happen to other contexts that have different characteristics to the context of this study. The study employed qualitative/descriptive design by utilizing four methods of data collection: (1) document analysis, (2) classroom observations, (3) questionnaire, and 4) interview. The analysis of the data was conducted throughout the study; once a piece of data was gained, it was analyzed right away. The data was coded and categorized which then allowed for generating findings. There are four major findings of this study: (1) the goal/objectives of the writing courses were appropriate to the studentsÃ¢â¬â¢ needs; however, the courses did not accommodate the realization of the goals/objectives, (2) the approaches/methodology, to some degree, were not contextual and did not meet the needs of the students, (3) the classroom management, to some extent, was not effective, and (4) the class/program resources, for certain aspects, were adequate to implement the goals/objectives of the courses. ÃÂ Key Words: curriculum, needs analysis, approach, method, classroom management